A new extant species of Electribius Crowson from Honduras (Coleoptera: Elateroidea: Artematopodidae) - Gimmel, Matthew L.; Bocakova, Milada (Zootaxa, 2015)
A new extant species of Electribius Crowson, E. llamae sp.n., is described from Cusuco National Park, Cortés Province, Honduras. This new species lacks one of the supposed autapomorphies of the genus; therefore the definition of the genus requires modification. A revised key to the known extant species is presented, and their known distributions are mapped.